Determinan Pencegahan Fraud Dalam Pengelolaan Dana Desa Dengan Komitmen Organisasi Sebagai Variabel Moderasi - Hesti Novitasari; Rida Perwita Sari (Journal of Economic, Bussines and Accounting (COSTING), 2022)
The purpose of this study was to determine the factors that influence fraud prevention in the management of village funds with organizational commitment as a moderating variable in the village government in Bojonegoro Regency. This study uses quantitative methods by using primary data sources through questionnaires. The population of this study is village officials whose villages are included in the category of independent villages in Bojonegoro Regency amounting to 103 villages. The research sample used simple random sampling method. Determination of the number of samples was carried out using the slovin technique with an inaccuracy rate of 10%, so that the minimum number of samples was 89 respondents. The results showed that the competence of the apparatus and the internal control system had a significant effect on preventing fraud in the management of village funds. Meanwhile, whistleblowing does not significantly affect the prevention of fraud in the management of village funds. Organizational commitment can moderate the competence of the apparatus and the internal control system to prevent fraud in the management of village funds. However, organizational commitment cannot moderate whistleblowing on fraud prevention in the management of village funds. Keywords: prevention fraud, competency apparatus, whistleblowing, internal control system, Organizational Commitment